Design of Atmega2560 Charge Controller Battery Using Static Bicycle - Agus Kiswantono; Achmad Zainul Muttakin; Bambang Purwahyudi (JEEE-U (Journal of Electrical and Electronic Engineering-UMSIDA), 2023)
At this time charging system has been increasingly advanced. advance with technological developments. One of them is the use of microcontrollers whose. applications are growing rapidly their application in charging. Battery Charge Controller is a charging device, to adjust the input voltage and output voltage of the battery so as not to overcharge and overdischarge. In this study, a battery charging control system with inputs produced by a pedal power plant was designed to drain the power from the power cycling generator to the Arduino Uno Microcontroller atmega 2560. The test that have been done on the Battery Charge Controller obtained a voltage of 14 volts, which causes the power supply to the load to be stable.